2023
DOI: 10.3389/fimmu.2023.1174289
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and characteristics influencing humoral response to COVID-19 vaccination in patients after allogeneic stem cell transplantation

Abstract: IntroductionVaccination against severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is approved and recommended for immunocompromised patients such as patients after allogeneic stem cell transplantation (allo-SCT). Since infections represent a relevant cause of transplant related mortality we analyzed the advent of immunization to SARS-CoV-2 vaccination in a bicentric population of allogeneic transplanted patients.MethodsWe retrospectively analyzed data of allo-SCT recipients in two German transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[89][90][91][92][93][94] Non-mRNA COVID-19 vaccines are also available, including nonreplicating competent adenovirus vector vaccines (AstraZeneca/ ChAdOx1-S and Johnson&Johnson/Jansen/Ad26.COV2-S), as well as the recombinant nanoparticle protein-based vaccine Novavax/NVX-CoV2373, although published safety and efficacy data are limited in HCT recipients. 75,[95][96][97] In a small study of hemato-oncological patients, Ad26.COV2-S appeared safe as a heterologous vaccine booster after two doses of BNT162b2 vaccine. 98 In hematology malignancy patients with diseases and treatments impacting B-cell immunity, in those who received two doses of ChAdOx1 vaccination followed by an mRNA vaccine, even in the absence of seroconversion robust SARS-CoV-2-specific T-cell immunity was documented.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[89][90][91][92][93][94] Non-mRNA COVID-19 vaccines are also available, including nonreplicating competent adenovirus vector vaccines (AstraZeneca/ ChAdOx1-S and Johnson&Johnson/Jansen/Ad26.COV2-S), as well as the recombinant nanoparticle protein-based vaccine Novavax/NVX-CoV2373, although published safety and efficacy data are limited in HCT recipients. 75,[95][96][97] In a small study of hemato-oncological patients, Ad26.COV2-S appeared safe as a heterologous vaccine booster after two doses of BNT162b2 vaccine. 98 In hematology malignancy patients with diseases and treatments impacting B-cell immunity, in those who received two doses of ChAdOx1 vaccination followed by an mRNA vaccine, even in the absence of seroconversion robust SARS-CoV-2-specific T-cell immunity was documented.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…Non‐mRNA COVID‐19 vaccines are also available, including non‐replicating competent adenovirus vector vaccines (AstraZeneca/ChAdOx1‐S and Johnson&Johnson/Jansen/Ad26.COV2‐S), as well as the recombinant nanoparticle protein‐based vaccine Novavax/NVX‐CoV2373, although published safety and efficacy data are limited in HCT recipients 75,95–97 . In a small study of hemato‐oncological patients, Ad26.COV2‐S appeared safe as a heterologous vaccine booster after two doses of BNT162b2 vaccine 98 .…”
Section: Vaccination In Hct Recipientsmentioning
confidence: 99%
“…People with hematological malignancies (HM) continue to represent a group of patients with a significantly higher risk of developing severe COVID‐19 compared with immunocompetent patients in terms of morbidity, hospitalization, and mortality, regardless of their vaccination status [ 6 ]. Response to vaccination is lower than in the general population with a positive serology in about 80% of HM patients after three or four doses of the SARS‐CoV2 vaccine [ 7 , 8 ]. Specific therapies, such as anti‐CD20 antibodies, BTK inhibitors, and stem cell transplantation, are known to be associated with lower rates of seroconversion [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Email: benedikt.obermayer@bihcharite.de [1][2][3] However, numerous studies have shown that hematologic patients in general, and allogeneic hematopoietic stem cell transplantation (ASCT) patients in particular, have a significantly weaker vaccine response than healthy controls, with a substantial number of patients failing to develop a protective immunity at all. [4][5][6][7][8][9][10][11][12][13][14] The current knowledge of vaccine response in patients after ASCT is limited to data on measurements of serological responses and in vitro measurements of specific T-cell immunity at various, commonly late time points after transplantation.…”
mentioning
confidence: 99%